MAKNA SIMBOLIS DAN NILAI PENDIDIKAN KARAKTER DALAM TRADISI TEMU MANTEN ADAT JAWA DI DESA MENANGGAL DALAM PERSPEKTIF ETNOLINGUISTIK - Nur Wahidatul Fikriyah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2019)
This study aiming to describe the lexical meaning and cultural meaning in the procession of the Temu Manten tradition in the Menanggal village Mojosari district. In this study, researchers took the object of research regarding the lexical and cultural meaning in the procession of the Temu Manten tradition in the Menanggal village Mojosari district. Research data can be obtained using interview, observation and documentation methods. The subjects in this study were community leaders and bridal makeup located in the Menanggal village. This type of research used in this research uses descriptive qualitative methods. The data validation techniques which are data reduction, data verification, and data display. The results of the study showed that the processions of Temu Manten tradition had 12 processions sophisticated, betel throwing, circling, stepping on eggs, wiji dadi, dringking parem, holding the bride, sungkem, scales, turquoise, feeding, and carnival. The results of the study also showed that there were 10 syimbols in the procession of the Temu Manten namely Janur yellow, betel leaves, broom sticks, eggs, flower flowers, drinking water, sindur cloth, change, rice and cooked rice. The meanings of the symbol of the Temu Manten procession are analyzed using lexical meanings and cultural meanings. Keywords : Ethnolinguistics, Temu Manten Tradition, Lexical and Cultural Meaning